Political poetry across the centuries - Günther, Hans Christian. (Studies on the Interaction of Art, Thought and Power, 2016)
The volume dedicates itself to the rather neglected field of political poetry and offers a broad perspective across the centuries from Plato until the post-war period. The first part describes the social function of poetry in Plato, his reception in Heidegger and in Ezra Pound's poetry. A contribution on Milton complements this with a great poet`s reflection on central political questions. The second part, pre 20th century, is rounded off by two rulers from the edges of Europe or Asia who left their mark both on history and on the literary history of their country: the Georgian king Teimuraz I and the Persian ruler Shah Ismail. This theme is continued in the last contribution dedicated to an outstanding combination of political and poetic talent from recent history, Mao Zedong. Two other contributions refer to the epoch of WWI, Europe`s big cultural caesura, and they dedicate themselves to two eminently influential figures, Stefan George and Vladimir Mayakowsky.